Dipole reorientation and local density of optical states influence the emission of light-emitting electrochemical cells. Issue 1 (5th December 2019) - Jiménez-Solano, Alberto; Martínez-Sarti, Laura; Pertegás, Antonio; Lozano, Gabriel; Bolink, Henk J.; Míguez, Hernán
Abstract : The joint effect of dipole reorientation and optical environment of the generation zone in LECs determines both the brightness and the directionality of the device. Abstract : Herein, we analyze the temporal evolution of the electroluminescence of light-emitting electrochemical cells (LECs), a thin-film light-emitting device, in order to maximize the luminous power radiated by these devices. A careful analysis of the spectral and angular distribution of the emission of LECs fabricated under the same experimental conditions allows describing the dynamics of the spatial region from which LECs emit, i.e. the generation zone, as bias is applied. This effect is mediated by dipole reorientation within such an emissive region and its optical environment, since its spatial drift yields a different interplay between the intrinsic emission of the emitters and the local density of optical states of the system. Our results demonstrate that engineering the optical environment in thin-film light-emitting devices is key to maximize their brightness.